COMPARISON OF MANAGERIAL IMPLICATIONS FOR UTILIZATION OF VARIABLE COSTING AND THROUGHPUT ACCOUNTING METHODS - Novak, Petr (Journal of Applied Engineering Science, 2016)
The aim of the paper is to compare the principles, information outputs and consequent managerial implications of the variable costing method and throughput accounting, according to their different perceptions of cost variability. These two approaches could give rise to various product mix decisions and findings relating to effect on profitability. The paper also provides a practical example of limitations experienced on two production lines for certain items. Comparison is made between these two approaches as to which elicits a relevant decision on production mix. Both the variable costing method and throughput accounting represent very similar methods based on variable costs that do not reflect fixed costs. Variable costing methods examine costs that change in accordance with volume of output. On the contrary, throughput accounting merely acknowledges total variable costs, and focuses on limitations which exist in a given company